Impact of Thyroid Autoimmunity in euthyroid women on the outcomes of In Vitro Fertilization. (July 2021) - Hamad, Ahed; Alhalabi, Nawras; Nmr, Nazht; Abbas, Fatima; Al-Hammami, Hisham; Ibrahim, Nazir; Alhalabi, Marwan
Abstract: Objective: Infertility is inadequately acknowledged as a problem in developing countries. Thyroid Autoimmunity (TAI) has been neatly investigated for its association with unfavorable pregnancy and reproductive consequences. We aim to evaluate Clinical Pregnancy Rate (CPR) as a primary outcome following In Vitro Fertilization/Intra Cytoplasmic Sperm Injection (IVF/ICSI) in women with Thyroid Autoimmunity (TAI). Methods: A Retrospective cohort study included 584 women who underwent IVF/ICSI treatment between November 2012 and April 2017 in Orient Hospital, Damascus, Syria. Patients were tested for TAI before IVF/ICSI procedure. Results: CPR did not significantly differ between TAI positive and TAI negative groups (p > 0.05). Subgroup analysis for only primary infertility patients showed a statistically significant difference in CPR between TAI positive and TAI negative groups. Conclusion: Although several arguments were in favor of the relation between IVF/ICSI outcomes and Thyroid autoimmune disease, the presence of TAI positivity did not adversely affect the clinical pregnancy rate. Highlights: Thyroid Autoimmunity has been investigated for its association with unfavorable pregnancy and reproductive consequences. The prevalence of TAI in Syrian women having IVF/ICSI is 25.3%. The positivity of Thyroid Autoimmunity did not adversely affect the clinical pregnancy rate for women underwent IVF/ICSI. Screening of Thyroid Autoimmunity constitutes a financial burden on patients more than its benefit. The findings highlight the infertility aspects of the Syrian population.